PAM4 enzyme immunoassay alone and in combination with CA 19‐9 for the detection of pancreatic adenocarcinoma. Issue 3 (16th August 2012) - Gold, David V.; Gaedcke, Jochen; Ghadimi, B. Michael; Goggins, Michael; Hruban, Ralph H.; Liu, Mengling; Newsome, Guy; Goldenberg, David M.
Abstract BACKGROUND: The monoclonal antibody PAM4 has high specificity for pancreatic ductal adenocarcinoma (PDAC), as well as its precursor lesions, but has not been found to be reactive with normal and benign pancreatic tissues. The objective of the current study was to evaluate a PAM4‐based serum enzyme immunoassay alone and in combination with the carbohydrate antigen (CA) 19‐9 assay for the detection of PDAC, with particular attention to early stage disease. METHODS: Sera from patients with confirmed PDAC (N = 298), other cancers (N = 99), benign disease of the pancreas (N = 120), and healthy adults (N = 79) were evaluated by a specific enzyme immunoassay for the concentration of PAM4 and CA 19‐9 antigen levels by blinded analyses. All tests for statistical significance were 2‐sided. RESULTS: The overall sensitivity for PAM4 detection of PDAC was 76%, with 64% of patients with stage I disease also identified. The detection rate was considerably higher (85%) for patients with advanced disease. The assay demonstrated high specificity compared with benign pancreatic disease (85%), with a positive likelihood ratio of 4.93. CA 19‐9 provided an overall sensitivity of 77%, and was positive in 58% of patients with stage I disease; however, the specificity was significantly lower for CA 19‐9 (68%), with a positive likelihood ratio of 2.85 (P = .026 compared with PAM4). It is important to note that a combined PAM4 and CA 19‐9 biomarker serum assay demonstrated an improved sensitivity (84%) for the overall detection of PDAC without a significant loss of specificity (82%) compared with either arm alone. CONCLUSIONS: The PAM4 enzyme immunoassay identified approximately two‐thirds of patients with stage I PDAC with high discriminatory power with respect to benign, nonneoplastic pancreatic disease. These results provide a rationale for testing patient groups considered to be at high risk for PDAC with a combined PAM4 and CA 19‐9 biomarker serum assay for the detection of early stage PDAC. Cancer 2013. © 2012 American Cancer Society.